Antipredator behaviour as a major determinant of prey altitudinal movements: the wolf and the chamois - Valerio Orazi; Matteo Panaccio; Sandro Lovari; Irene Belardi; Achaz von Hardenberg; Bruno Bassano; Francesco Ferretti (Frontiers in Zoology)
Abstract Background Predators have the potential to affect prey ecology through both direct effects on population dynamics or indirect effects on behaviour, e.g., by triggering antipredator strategies. Direct effects of predation on single prey species may be limited in ecosystems hosting alternative prey, possibly being overwhelmed by indirect effects. The novel exposure to a predator would provide the opportunity to test for immediate prey responses, but information is scanty for areas recolonised by carnivores. We took advantage of the natural expansion of the wolf Canis lupus in a protected area of western Alps hosting five ungulate species to test the potential for direct versus indirect effects on the main prey, i.e., a widespread mountain herbivore (the Northern chamois Rupicapra rupicapra). After verifying the contribution of the latter to the diet of the former, we used a semi-experimental (before vs. after) approach by comparing chamois demography, elevation used and group size between two valleys with different recolonisation time (Site A: medium-term vs. Site B: short-term). Results Scat analyses (N = 335 samples) indicated that chamois were the staple in the wolf diet in both valleys. Analyses of counts throughout 21 years supported no direct effect of wolf on chamois abundance and survival. Following wolf recolonisation, female chamois (n = 3594 observations) in Site A were observed at average elevations 137 m higher compared to the former period, and a concurrent decrease of group size was reported; these effects were not detected in Site B. The same trend was not observed in temperature, precipitation or NDVI, providing no support to a weather- or resource-mediated uplift. Conclusions Although direct/indirect effects of current changes in weather patterns on the observed uplift of chamois may not be ruled out, our results suggest antipredator behaviour as a main determinant of chamois upshift. Finally, we discuss the role of indirect versus direct short-term prey responses in complex ecosystems.